5-ALA-guided tumor resection during awake speech mapping in gliomas located in eloquent speech areas: Single-center experience - Sergey A. Goryaynov; Svetlana B. Buklina; Ivan V. Khapov; Artyom I. Batalov; Alexander A. Potapov; Igor N. Pronin; Artem U. Belyaev; Andrey A. Aristov; Vadim U. Zhukov; Galina V. Pavlova; Galina V. Pavlova; Galina V. Pavlova; et al. (Frontiers in Oncology, 2022)
BackgroundAchieving maximal functionally safe resection of gliomas located within the eloquent speech areas is challenging, and there is a lack of literature on the combined use of 5-aminolevulinic acid (5-ALA) guidance and awake craniotomy.ObjectiveThe aim of this study was to describe our experience with the simultaneous use of 5-ALA fluorescence and awake speech mapping in patients with left frontal gliomas located within the vicinity of eloquent speech areas.Materials and methodsA prospectively collected database of patients was reviewed. 5-ALA was administered at a dose of 20 mg/kg 2 h prior to operation, and an operating microscope in BLUE400 mode was used to visualize fluorescence. All patients underwent surgery using the “asleep–awake–asleep” protocol with monopolar and bipolar electrical stimulation to identify the proximity of eloquent cortex and white matter tracts and to guide safe limits of resection along with fluorescence guidance. Speech function was assessed by a trained neuropsychologist before, during, and after surgery.ResultsIn 28 patients operated with cortical mapping and 5-ALA guidance (12 Grade 4, 6 Grade 3, and 10 Grade 2 gliomas), Broca’s area was identified in 23 cases and Wernicke’s area was identified in 5 cases. Fluorescence was present in 14 cases. Six tumors had residual fluorescence due to the positive speech mapping in the tumor bed. Transient aphasia developed in 14 patients, and permanent aphasia developed in 4 patients. In 6 patients operated with cortical and subcortical speech mapping and 5-ALA guidance (4 Grade 4, 1 Grade 3, and 1 Grade 2 gliomas), cortical speech areas were mapped in 5 patients and subcortical tracts were encountered in all cases. In all cases, resection was stopped despite the presence of residual fluorescence due to speech mapping findings. Transient aphasia developed in 6 patients and permanent aphasia developed in 4 patients. In patients with Grade 2–3 gliomas, targeted biopsy of focal fluorescence areas led to upgrading the grade and thus more accurate diagnosis.Conclusion5-ALA guidance during awake speech mapping is useful in augmenting the extent of resection for infiltrative high-grade gliomas and identifying foci of anaplasia in non-enhancing gliomas, while maintaining safe limits of functional resection based on speech mapping. Positive 5-ALA fluorescence in diffuse Grade 2 gliomas may be predictive of a more aggressive disease course.